Rest in pizza ebook - Cavender, Chris (Pizza Lovers Mystery., 2012)
When a celebrity chef rolls into town—only to fall down dead—it's up to the proprietors of a pizzeria to catch a killer in this small town cozy mystery. Cozy towns like Timber Ridge, North Carolina—the home of Eleanor Swift's delectable pizzeria, A Slice of Delight—don't take well to prima donna celebrities. So no one is pleased when TV host and famous chef Antonio Benet roars into town for a book signing. In short order, he manages to insult Eleanor, her saucy sister Maddy, and everyone else within earshot. But while Antonio's antics are in poor taste, his murder is truly foul. While Eleanor may have had a motive, the investigation is piled high with suspects. Does Cindy the bookstore owner have some deep secrets to dish? Did Benet's personal assistant have some secret pie-in-the-sky ambitions? And what about his producer, who may have soured to the star chef? With her freedom on the chopping block, Eleanor needs to deliver the real killer before she finds a knife in her back. Includes a delicious pizza recipe!